Awareness and factors influencing breast reconstruction in the Gaza Strip: a cross-sectional study. (21st February 2018) - Alaloul, Enas; Elshami, MohammedRaed; Elessi, Khamis; Awad, Israa; Nemer, Huda Abu; Khader, Esraa; Baraka, Heba; Alhelu, Alaa
Abstract: Background: Women are usually given two options after a mastectomy. They can either wear a prosthesis or have a breast reconstruction. Unfortunately, many women in the Gaza Strip are unaware of these options. The aim of this study was to shed light on the awareness and sociocultural factors in women who underwent mastectomy before choosing between options. Methods: In this cross-sectional study, we recruited patients who underwent mastectomy in the Gaza Strip. All participants completed a face-to-face questionnaire between Aug 1, 2015, and April 30, 2016. Verbal consent was obtained from all participants. Findings: 173 women with a mean age 51 years (SD 10) were enrolled in this study. 90 (52%) women had low income, and 36 (21%) women had a first-degree relative with breast cancer. 133 (77%) women underwent radical mastectomy, and 29 (17%) women had breast-conserving surgery. 96 (55%) women had tried a breast prosthesis to gain confidence, and 72 (42%) women were unaware of the availability of breast reconstruction in the Gaza Strip. 161 (93%) women expressed a strong desire to have breast reconstruction surgery, whereas 12 (7%) women expressed no interest. The preference for breast reconstruction surgery was justified as a way of regaining positive attitudes from others (135 [84%] women), improving romance and satisfying their husbands (116 [72%]), and regaining self-confidence (37 [23%]). Being unconcerned about the physical appearance was the most common explanation for refusing breast reconstruction surgery (47 [29%] women), whereas 18 (11%) women had a fear of getting unsatisfactory results. Interpretation: When opting for breast reconstruction surgery, patients appear to be affected by prior knowledge, societal attitudes, body appearance, and romantic relationships. The findings suggest that assessing women's desires, goals, and expectations could help improve service delivery after mastectomy. Efforts should be made to spread knowledge and awareness of breast reconstruction options for women having a mastectomy in the Gaza Strip. Funding: None.